Indoor air pollution and behavioral factors affecting to COVID-19 transition - Ehsanifar, Mojtaba; Rafati, Mehravar; Yavari, Zeinab (Journal of Community Medicine and Health Solutions, 2022)
Environmental and behavioral factors are very important for exposure to airborne SARS-CoV-2. Indoor environments are related to infection events, including super-spreader events and outbreaks. Indoor, poorly ventilated, and crowded areas, such as restaurants, cinemas, and bars can be effective in the accumulation of aerosols full of viruses, especially if people are in conversations and stay there for a long time period. At longer distances (more than 1.5 meters), small aerosols that can stay in the air for a longer period of time are dominant. The super-spreader events in which people have been infected at a distance away show that this remote transmission occurs. The exposure risk to longer intervals is likely to be more in domestic environments and indoor spaces that lack sufficient ventilation. Layer interventions are of fundamental importance. Therefore, it is important to take preventive measures as much as possible and follow them as carefully as possible, because no intervention alone will be effective in eliminating the risk. These include spacing, lining, hand hygiene, filtration, and ventilation.